2018
DOI: 10.1007/s11010-018-3294-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into exchange factor directly activated by cAMP (EPAC) as potential target for cancer treatment

Abstract: Cancer remains a global health problem and approximately 1.7 million new cancer cases are diagnosed every year worldwide. Although diverse molecules are currently being explored as targets for cancer therapy the tumor treatment and therapy is highly tricky. Secondary messengers are important for hormone-mediated signaling pathway. Cyclic AMP (cAMP), a secondary messenger responsible for various physiological processes regulates cell metabolism by activating Protein kinase A (PKA) and by targeting exchange prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 120 publications
0
36
0
Order By: Relevance
“…There is also the possibility that an improved therapeutic window might be achieved by combining sub-optimal doses of PDEi's with ineffective doses of downstream-target activators, which would result in an effective combined dose only in tissues and subcellular compartments where both molecules were present (e.g., (295)). Indeed, PKA, PKG, and Epacs have been implicated as therapeutic targets in their own right for a number of indications for which PDEi's are being pursued, including diseases of the cardiovascular, immune, and nervous systems as well as cancer (e.g., (129,130,(296)(297)(298)(299)(300)). Further, several studies in a variety of tissues have attributed the beneficial effects of PDEi's to the activation of PKA, PKG and/or Epac (e.g., (135,(301)(302)(303)).…”
Section: Discussionmentioning
confidence: 99%
“…There is also the possibility that an improved therapeutic window might be achieved by combining sub-optimal doses of PDEi's with ineffective doses of downstream-target activators, which would result in an effective combined dose only in tissues and subcellular compartments where both molecules were present (e.g., (295)). Indeed, PKA, PKG, and Epacs have been implicated as therapeutic targets in their own right for a number of indications for which PDEi's are being pursued, including diseases of the cardiovascular, immune, and nervous systems as well as cancer (e.g., (129,130,(296)(297)(298)(299)(300)). Further, several studies in a variety of tissues have attributed the beneficial effects of PDEi's to the activation of PKA, PKG and/or Epac (e.g., (135,(301)(302)(303)).…”
Section: Discussionmentioning
confidence: 99%
“…As far as leukemia is concerned, to our knowledge, the cytotoxic effect of GSKJ4 has only been reported in acute lymphoblastic leukemia ( Ntziachristos et al, 2014 ), whereas the combination of all trans retinoic acid (ATRA) and GSKJ4 has been very recently described to significantly increase the cell death compared with ATRA or GSKJ4 treatment alone in PML-RARα-positive leukemic cells ( Rejlova et al, 2018 ). On the other hand, increased intracellular cAMP concentration plays a well-established role in leukemic cell maturation and proliferation ( Shayo et al, 2004 ; Copsel et al, 2011 ; Murray and Insel, 2013 ) and, more in general, cAMP, either via protein kinase A (PKA)-dependent or PKA-independent mechanisms, affects numerous cellular functions and is considered very relevant to cancer ( Sapio et al, 2014 ; Kumar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…XuS et al found that prostaglandin E2 (PGE2) receptor EP4 signaling activates the cyclic (c)-AMP signaling pathway, which may be closely related to the occurrence of prostate cancer [26]. It is reported by Kumar N1 that the cAMP signaling pathway was associated with non-small cell lung cancer [27]. Thus, it is possible that RUNX1 mutations may affect development and prognosis of AML through the ECMreceptor interaction pathway and cAMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%